2008
DOI: 10.1089/neu.2008.0593
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D2Potentiates Axon Regeneration

Abstract: To date, the use of autograft tissue remains the "gold standard" technique for repairing transected peripheral nerves. However, the recovery is suboptimal, and neuroactive molecules are required. In the current study, we focused our attention on vitamin D, an FDA-approved molecule whose neuroprotective and neurotrophic actions are increasingly recognized. We assessed the therapeutic potential of ergocalciferol--the plant-derived form of vitamin D, named vitamin D2--in a rat model of peripheral nerve injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 55 publications
2
58
0
3
Order By: Relevance
“…Vitamin D deficiency has also been suggested to elevate brain damage and attenuate the affects of other treatments in traumatic brain injury cases (Cekic et al 2009). One study showed that vitamin D potentiates axon regeneration by significantly increasing axogenesis and axon diameter in a rat model of peripheral nerve injury (Chabas et al 2008). Thus vitamin D may have a potential role in the treatment of CNS injuries (Kiraly et al 2006;Cekic et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency has also been suggested to elevate brain damage and attenuate the affects of other treatments in traumatic brain injury cases (Cekic et al 2009). One study showed that vitamin D potentiates axon regeneration by significantly increasing axogenesis and axon diameter in a rat model of peripheral nerve injury (Chabas et al 2008). Thus vitamin D may have a potential role in the treatment of CNS injuries (Kiraly et al 2006;Cekic et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…5E-G). Aside from appendage regeneration, vitamin D has been shown to influence liver, axon and skeletal muscle regeneration (Ethier et al, 1990;Chabas et al, 2008;Stratos et al, 2013). It will be interesting to examine whether the regulation of vitamin D signaling is important in additional regenerative contexts.…”
Section: Research Articlementioning
confidence: 99%
“…There is strong evidence that vitamin D is involved in neuroprotection through various mechanisms: up-regulation of neurotrophic factors, antioxidative mechanisms, neuronal calcium regulation, nerve growth factor modulation [33][34][35][36][37], regulation of the toxicity of reactive oxygen species [38] and through immunomodulation and vasoprotection [7,10]. However, it is also possible that lower vitamin D levels could be a common factor in diseases that share neuro-inflammatory dysfunction as observed in MS.…”
Section: Discussionmentioning
confidence: 99%